Case Report: DNAAF4 Variants Cause Primary Ciliary Dyskinesia and Infertility in Two Han Chinese Families - Guo, Ting; Lu, Chenyang; Yang, Danhui; Lei, Cheng; Liu, Ying; Xu, Yingjie; Yang, Binyi; Wang, Rongchun; Luo, Hong (Frontiers in Genetics, 2022)
Background: Primary ciliary dyskinesia (PCD) is a rare genetic disorder, predominantly autosomal recessive. The dynein axonemal assembly factor 4 (DNAAF4) is mainly involved in the preassembly of multisubunit dynein protein, which is fundamental to the proper functioning of cilia and flagella. There are few reports of PCD-related pathogenic variants of DNAAF4, and almost no DNAAF4-related articles focused on sperm phenotype. Moreover, the association between DNAAF4 and scoliosis has never been reported, to the best of our knowledge. Materials and Methods: We recruited two patients with a clinical diagnosis of PCD. One came from a consanguineous and another from a non-consanguineous family. Clinical data, laboratory test results, and imaging data were analyzed. Through whole exome sequencing, immunofluorescence, electron microscopy, high-speed video microscopy analysis, and hematoxylin–eosin (HE) staining, we identified the disease-associated variants and validated the pathogenicity. Results: Proband 1 (P1, F1: II-1), a 19-year-old man, comes from a non-consanguineous family-I, and proband 2 (P2, F2: II-1), a 37-year-old woman, comes from a consanguineous family-II. Both had sinusitis, bronchiectasis, situs inversus, and scoliosis. P1 also had asthenoteratozoospermia, and P2 had an immature uterus. Two homozygous pathogenic variants in DNAAF4 (NM_130810.4), c.988C > T, p.(Arg330Trp), and DNAAF4 (NM_130810.4), c.733 C > T, p.(Arg245*), were identified through whole exome sequencing. High-speed microscopy analysis showed that most of the cilia were static in P1, with complete static of the respiratory cilia in P2. Immunofluorescence showed that the outer dynein arms (ODA) and inner dynein arms (IDA) were absent in the respiratory cilia of both probands, as well as in the sperm flagellum of P1. Transmission electron microscopy revealed the absence of ODA and IDA of respiratory cilia of P2, and HE staining showed irregular, short, absent, coiled, and bent flagella. Conclusion: Our study identified a novel variant c.733C > T, which expanded the spectrum of DNAAF4 variants. Furthermore, we linked DNAAF4 to asthenoteratozoospermia and likely scoliosis in patients with PCD. This study will contribute to a better understanding of PCD.